Jumpy, Patient Frog Named Sally And A Math Problem About Her Life-V

A frog, namely, Sally, is jumping about the vertices of a triangle, A B C ABC . Each time, she jumps to an adjacent vertex with equal probability. In how many ways can she get from A A to A A in 132435 132435 jumps?

Can you generalise for n n jumps as a little bonus?

This problem is a part of my froggy, soggy set .


The answer is 2.693E+39866.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Abhishek Sinha
Apr 19, 2015

Let N ( x , y ; k ) N(x,y;k) denote the number of ways of getting from vertex x x to y y in k k jumps. Then we have the following recursive equations : N ( A , A ; k ) = N ( B , A ; k 1 ) + N ( C , A ; k 1 ) ( 1 ) N(A,A;k)=N(B,A;k-1)+N(C,A;k-1)\hspace{10pt}(1) N ( B , A ; k ) = N ( A , A ; k 1 ) + N ( C , A ; k 1 ) ( 2 ) N(B,A;k)=N(A,A;k-1)+N(C,A;k-1)\hspace{10pt}(2) Due to symmetry of the points B B and C C , we have N ( B , A ; k ) = N ( C , A ; k ) = g k (say) N(B,A;k)=N(C,A;k)=g_k\hspace{20pt}\text{(say)} Also, let N ( A , A ; k ) = f k N(A,A; k)=f_k . Then equations (1) and (2) are simplified as f k = 2 g k 1 , ( 3 ) f_k=2g_{k-1}, \hspace{10pt}(3) g k = f k 1 + g k 1 ( 4 ) g_k=f_{k-1}+g_{k-1}\hspace{10pt}(4) Eliminating f k f_k from Eqns (3) and (4), we have g k = g k 1 + 2 g k 2 g_k=g_{k-1}+2g_{k-2} with the initial conditions g 1 = 1 , g 2 = 1 g_1=1,g_2=1 . Solving the above linear recurrence for g k g_k , we have g k = 1 3 ( 2 k ( 1 ) k ) g_k=\frac{1}{3}\big(2^{k}-(-1)^k\big) And hence f k = 2 3 ( 2 k 1 ( 1 ) k 1 ) f_k=\frac{2}{3}\big(2^{k-1}-(-1)^{k-1}\big) The above is an exact solution for k k jumps. For large k k , the above may be simplified as f k 1 3 2 k f_k\approx \frac{1}{3}2^{k} Hence for k = 132435 k=132435 , the answer follows (after taking logarithm to the base of 10 10 and then exponentiating the result).

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...